Investigations on Terminalia Arjuna Fruits: Part 2- Isolation of Comound from ethyl Acetate Fraction (Bangladesh Journal of Scientific and Industrial Research, 2008)
No Abstract Available.Bangladesh J. Sci. Ind. Res. 43(1), 145, 2008